Moral Education Values in the Animation Series of I'm the Best Muslim - Shafira Ramadanty; Abd Madjid (At Turots: Jurnal Pendidikan Islam, 2023)
The research aims to analyze moral education values, existing in the animation series I'M THE BEST MUSLIM based on the scene and script in the animation series and referred to various types of moral education values. The research was library research and utilized the qualitative approach. The source of data was nine of twenty-eight episodes of the animation series I'M THE BEST MUSLIM. Then, the data collection technique was the primary documentation. In addition, the data analysis included data collection, data selection, data reviewing, analysis, descriptive interpretation, and conclusion. The result indicates that nine episodes of the animation series I'M THE BEST MUSLIM had akhlak education values, such as Allah SWT., Rasulullah SAW., personal, family, social, and national.